Capacitive imaging for adhesive bonds and quality evaluation. (16th October 2020) - Huang, Xuhui; Hamilton, Ciaron; Li, Zonglin; Udpa, Lalita; Udpa, Satish S.; Deng, Yiming
Abstract : Defective adhesive bonds pose significant threats towards structural integrity due to reduced joint strength. The nature of the adhesion of two solids remains poorly understood since the adhesion phenomenon is relevant to so many scientific and technological areas. A concept that has been gaining our attention from the perspective of non-destructive testing is the properties discontinuity of the adhesion. Discontinued properties depend significantly on the quality of the interface that is formed between adhesive and substrate. In this research, discontinued electrical properties at the interface are considered. The simplified model is free from multidisciplinary knowledge of chemistry, fracture mechanics, mechanics of materials, rheology and other subjects. From a practical standpoint, this emphasizes the need to establish a good relationship between electrical properties of adhesive bonds and corresponding measurements. Capacitive imaging (CI) is a technique where the dielectric property of an object is determined from external capacitance measurements. Thus, it is potentially promising since adhesive and substrate differ in terms of dielectric property. At the interface between adhesive and substrate, discontinuity of the dielectric properties causes abrupt changes in electric field spatial distribution and thus alters capacitance measurement by simulating defects in adhesive joints regarding permittivity uncertainties. Further understanding of the cause of degraded adhesion quality can be obtained. This article is part of the theme issue 'Advanced electromagnetic non-destructive evaluation and smart monitoring'.